The Study of Job Satisfaction : Exploring Work-Life Balance, Job Stress, and Burnout - Nurjihan Erlinda; Dewi Khrisna Sawitri (Dinasti International Journal of Education Management And Social Science, 2025)
The present research examines the influence of work life balance and job stress on job satisfaction, with burnout as a mediating variable among employees of the Operations Directorate at public service company in Surabaya. Job satisfaction is essential as it affects employee motivation and productivity. The research uses a quantitative approach with 70 respondents selected using Slovin’s formula and analyzed through the SEM-PLS method. The results show that maintaining work-life balance contributes positively and meaningfully to job satisfaction, while job stress has a negative and significant effect. Additionally, burnout mediates the effect of both work-life balance and job stress on job satisfaction, indicating that less burnout is related to higher levels of job satisfaction.